Design of a shunt active caused by nonlinear loads power filter to mitigate the harmonics caused by nonlinear loads - Soomro, Dur Muhammad (2015)
Application of non-linear electrical devices has It may lead equipment (connected to it) to overhea application of three-phase shunt active power filter by nonlinear loads. To obtain result for this paper, the MATLAB / Simulink was used as a simulation tool. results are within the recommended IEEE-519 standard almost unity. led to a distortion in the output sine waveforms of source current and voltage overheat and sometimes cause damage. This paper concentrates on the design and (SAPF) by using p-q theory to mitigate the harmonics which are created i.e. less than 5% and also the power factor (s voltage. The achieved PF) of the system to